Hyperinsulinemic Euglycemia Therapy for Acute Nitroglycerin Poisoning: Case Report - Vasheghani Farahani, Maryam; Soltani, Siamak; Marashi, Sayed Mahdi (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Nitroglycerin, a vasodilator, is commonly administered to treat ischemic heart disease. Adverse effects after toxicity are light-headedness, nausea, blurry vision, and syncope due to low systolic blood pressure as well as methemoglobinemia. A 19-year-old female was admitted to our toxicology department after suicidal ingestion of 320 mg extended-release nitroglycerin about 45 minutes before the admission. She was conscious, and her initial blood pressure was 98/65 mm Hg, which was decreased to 77 mmHg within 1.5 hours despite administration of 1 liter of normal saline. Due to severe hypotension, norepinephrine infusion was started for systolic blood pressure maintenance above 80mm Hg; however, she started complaining of palpitation and chest pain. So, the dose of norepinephrine was reduced, and glucose, insulin, and potassium protocol were started. After 3 hours of therapy, her hemodynamic condition stabilized with systolic blood pressure above 90mm Hg; hence norepinephrine was discontinued. She was discharged on the 3rd day after the psychiatric consultation, with regular clinical and paraclinical examinations.